EU Policy on Deepening Liberal Democracy: a Case Study of the Baltic States - Khoma, Nataliia; Vdovychyn, Ihor (Wydawnictwo Naukowe Wydziału Nauk Politycznych i Dziennikarstwa UAM, 2021)
The issues of the EU’s activities concerning the quality of democracy in member states are studied. On the examples of Estonia, Latvia and Lithuania, the effectiveness of EU projects to continue the liberal-democratic transformation in member states with a post-totalitarian past where the risk of regression of democracy remains, is assessed. The current goals of the EU are described as being insufficient in terms of properly preventing and counteracting the decline of the quality of democracy, as well as for inculcating the values of liberal democracy. The need to intensify the EU’s activities in the direction of monitoring the observance of democratic standards is explained by the stagnation/regression of the quality of democracy in the countries of the recent EU enlargements, including the Baltic States. The actions of the EU’s institutions towards member states, where democracy shows stagnation/regression, are assessed as inconsistent, due to the possible consequences of this destructive process. The EU’s lack of attention to strengthening the values on which the EU is based is emphasized, which is seen as the main reason for the present deterioration in the quality of democracy. The requirement to construct a new format of European democracy and new mechanisms to ensure its quality is highlighted.

Badana jest skuteczność działań UE w zakresie jakości demokracji w państwach członkowskich. Na przykładzie Estonii, Łotwy i Litwy oceniano skuteczność unijnych projektów dotyczących kontynuacji transformacji liberalno-demokratycznej w państwach członkowskich z przeszłością posttotalitarną, w których utrzymuje się ryzyko regresu demokracji. Obecne cele UE scharakteryzowano jako niedostatecznie ukierunkowane na odpowiednie zapobieganie i przeciwdziałanie spadkowi jakości demokracji, zakorzenienie wartości demokracji liberalnej. Konieczność zintensyfikowania działań UE w kierunku monitorowania przestrzegania standardów demokratycznych tłumaczy się stagnacją/regresją jakości demokracji w krajach ostatnich rozszerzeń UE, w tym w państwach bałtyckich. Działania instytucji UE wobec państw członkowskich, w których demokracja znajduje się w stagnacji/regresie, zostały ocenione jako niezgodne z możliwymi konsekwencjami tego destrukcyjnego procesu. Podkreśla się brak zainteresowania UE umacnianiem wartości, na których opiera się UE, co jest postrzegane jako główna przyczyna obecnego pogorszenia się jakości demokracji. Podkreślono potrzebę skonstruowania nowego formatu demokracji europejskiej, nowych mechanizmów gwarantujących jej jakość.
Polityka UE dotycząca pogłębienia liberalnej demokracji: przykład państw bałtyckich
Keywords: liberal democracy; Baltic States; EU; defects of democracy; quality of democracy; demokracja liberalna; państwa bałtyckie; UE; wady demokracji; jakość demokracji